Matrizes iônicas: detecção e quantificação de cianotoxinas por maldi-ms - Bronzel Júnior, João Luiz [UNESP] (2015)
The Matrix-Assisted Laser Desorption/Ionization technique was one of the ionization sources responsible for revolutionizing Mass Spectrometry, making possible its application to labile and high molecular weight molecules, such as proteins. Despite its great development, this technique still has some limitations like the selection of the matrix and the sample preparation method. These factors determine the reproducibility of analysis and the m/z application range. Initially, in this work, we analyzed different cyanobacteria strains by MALDI-TOF-MS, in order to check for new analytes to be monitored using ionic matrices. Subsequently, the characteristics of these matrices, the sample preparation method, the composition of the analyte and laser intensity of the MALDI source were evaluated aiming to select the best methodologies of analysis. After this step, the selected ionic matrices and methodologies have been applied in the detection and quantification of cianotoxins and analysis of pharmaceutical drugs by MALDI-MS. In this study we obtained as results: the differentiation of strains of cyanobacteria through the fingerprints obtained by MALDI-TOF-MS which allowed the detection of important metabolites; the detection of homoanatoxin-a, a low molecular weight cyanotoxin, directly from cyanobacteria cells; the development of a quantitative method for the analysis of microcystins with great precision; and the development of a new methodology for the detection of active compounds of medicines, increasing, therefore, the application range of MALDI technique.